Formulating direct sales customers’ satisfaction strategies : Application of Importance-Performance Analysis (IPA) approach / Rosidah Musa - Musa, Rosidah (Universiti Teknologi MARA Cawangan Pahang, 2005)
In highly competitive markets, customer satisfaction is a key driver in realising positive outcomes such as customer loyalty, customer retention and, ultimately profitability, thus making its measurement and management crucial. Despite its importance, the attempt to understand what makes customers satisfied remains a difficult task and this pose key challenge and is a critical management issue today. For these reasons customer satisfaction is the primary focus of this study. The data for this research was collected from 400 ustomers of the direct sales channel within three districts in Klang Valley via ‘drop off and collect’ survey technique. The present study aims to unravel the key attributes that drive customer satisfaction with the direct sales channel. Consequently, these attributes will be analysed in order to develop and formulate marketing strategies by utilising the Importance–Performance Analysis (IPA). IPA is an easy-to-use analytical technique that offers prescriptions for the management of customer satisfaction. The results have important implications for future research directions and management practise.